A Case Series of Three US Adults With Japanese Encephalitis, 2010–2012. Issue 5 (26th May 2014) - Hills, Susan L.; Stoltey, Juliet; Martínez, Diana; Kim, Paul Y.; Sheriff, Heather; Zangeneh, Ana; Eilerman, Sally R.; Fischer, Marc
<x xml:space="preserve">Abstract</x> Background Japanese encephalitis (JE) virus is the leading cause of vaccine‐preventable encephalitis in Asia. Although the risk for acquiring JE for most travelers to Asia is low, it varies based on the destination, season, trip duration, and activities. Methods We present case reports of three US adults who were infected with JE virus while traveling or residing in Asia. Results Among the three JE patients, the first made a 10‐day trip to mainland China and participated in outdoor activities in a rural area, the second had been resident in Taiwan for 4 months, and the third, fatal case was an expatriate living in South Korea. Conclusions JE should be considered in the differential diagnosis for any patient with an acute neurologic infection, who has recently been in a JE‐endemic country. Health‐care providers should assess the itineraries of travelers to JE‐endemic countries, provide guidance on personal protective measures to prevent vector‐borne diseases, and consider recommending JE vaccine for travelers at increased risk for JE virus infection.